TNF-α Dysregulation in Asthma: Relationship to Ongoing Corticosteroid Therapy - Susan Waserman; Jerry Dolovich; Mary Conway; Jean S Marshall (Canadian Respiratory Journal)
BACKGROUND: Tumour necrosis factor-alpha (TNF-α) is a major proinflammatory cytokine that is thought to be important in the pathogenesis of asthma. However, alterations in systemic regulation of this cytokine in asthma have not been examined in the context of corticosteroid therapy.